MADE 2 FADE: A Practical Strategy for Empowering Independence for Students With Disabilities. (September 2022) - Ingles, Kristina E.; Gilson, Carly B.; Pena, Humberto
Independence is a critical skill in preparing students with disabilities for success after high school. Secondary special education teachers equip their students toward task independence across skill domains (e.g., employment, independent living), yet there is little guidance regarding a simple and systematic way to do so. MADE 2 FADE (M2F) is a mnemonic developed to support special education teachers in data-driven decisions and implementation of research-based practices. This framework is designed to help teachers as they encourage their students with disabilities toward greater self-efficacy and skill mastery.